Accurate safty zone detemination during gas flaring (2009)
Gas flaring, a long-established but unacceptable practice in the Nigerian Petroleum industry, has deleterious effects on the environment. Research efforts have concentrated on using empirical formulae derived from experiments in predicting heat fluxes around a gas flare. However numerical method, which is capable of eliminating the severe inaccuracies in calculation from empirical formulae, is yet to be explored. The flare was considered as a three-dimensional turbulent jet issuing into a continuous cross flow of air. The momentum and scalar fluxes were approximated by the k-ε turbulence model and the resultant conservation equations were solved using the finite volume technique. The laminar flamelet concept was used to characterize the local thermochemical state of the combusting mixture, while the discrete transfer method was used to compute the radiative heat flux. A model for an accurate prediction of the heat flux at any point within the vicinity of a gas flare was developed. Thermal radiation profiles predicted at ground level exhibited Gaussian behaviour. Deviation of the predicted flux result at ground level estimated by the empirical formulae were between 15.0 and 35.0%. Based on the existing standard for maximum allowable radiation flux of 6.3 kW m-2, the model minimum safest distance from the flare was 1.1 m, whilst the empirical formulae gave minimum safest distances ranging between 0.8 and 1.4 m. This model had superior prediction capabilities than the existing empirical formulae. Safe distances could be deduced from heat flux standpoint for both humans and habitat using the model.